Trastorno por déficit de atención e hiperactividad y rendimiento académico de un estudiante de décimo año de educación básica de la Escuela Adolfo Paez del cantón Echeandía Provincia de Bolívar - García Guzmán, Eliana Angelita (2023)
Attention deficit hyperactivity disorder is a problem that generates repercussions for various dimensions of the students who suffer from it, hindering normal development in aspects that integrate their development in various contexts. Also known as hyperkinetic disorder, it also has a nature with neural bases that affects the cognitive functioning of the individual, altering processes such as attention, concentration, and even in solving problems of a complex nature such as the mathematical area. Academic performance is a multidimensional factor that is influenced by various factors, among the main ones is the teaching-learning process determined by actors such as teachers and the didactics they use during the delivery of the contents of the academic curriculum, as well as the support of the authorities of the institution regarding the administration of the necessary resources to make the educational processes viable. ADHD encompasses a series of signs and symptoms that are expressed through behavior, affecting mental processes and involving adequate stimulation through interaction with other individuals; due to the fact that experimentation constitutes a primary form of learning in the stage of adolescence where several skills acquired in previous stages are mastered.